DILEMA PENEGAKAN HUKUM DALAM KASUS PENYALURAN KREDIT USAHA RAKYAT (KUR): STUDI KASUS PADA BUMN - Yahya, Alvin; Fadhlulloh, Qolbi Hanif (CENDERAWASIH CONSTITUTIONAL REVIEW, 2025)
The distribution of People's Business Credit (KUR) by State-Owned Enterprises (BUMN) in Indonesia since 2007 has become one of the government's strategies to enhance access to financing for micro, small, and medium enterprises (MSMEs). Although this program aims to strengthen the capital of MSMEs and stimulate economic growth, challenges such as non-performing loans indicate a dilemma in law enforcement. Data from the Coordinating Ministry for Economic Affairs recorded that in 2023, the non-performing loan ratio reached 2.03%, which poses a burden of losses for banks and the state. Legal cases, such as the Supreme Court's ruling on collusion in the distribution of KUR, highlight the need for strict evaluation and oversight in managing this program. With a clear legal foundation, including the Limited Liability Company Law and Financial Services Authority Regulations, it is crucial for BUMN to adopt principles of prudence and transparency in every decision made. This research aims to evaluate the implications of state financial losses due to non-performing loans and the importance of accountability in managing KUR, as well as to provide recommendations for a more effective and accountable system.